2006
DOI: 10.1177/1090198106294895
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Drug Prevention Among At-Risk Adolescents: Effects of ALERT Plus

Abstract: In a recent randomized field trial, Ellickson et al. found the Project ALERT drug prevention curriculum curbed alcohol misuse and tobacco and marijuana use among eighth-grade adolescents. This article reports effects among ninth-grade at-risk adolescents. Comparisons between at-risk girls in ALERT Plus schools (basic curriculum extended to ninth grade with five booster lessons) and at-risk girls in control schools showed the program curbed weekly alcohol and marijuana use, at-risk drinking, alcohol use resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 39 publications
0
43
0
1
Order By: Relevance
“…Prevention programs may need to consider different strategies in changing attitudes towards drug use once marijuana use has begun. For example, one school drug-prevention program based on three theoretical models (health belief model- Rosenstock et al, 1988, social learning model-Bandura, 1985, and the self-efficacy theory-Bandura, 1977) was able to decrease positive attitudes towards marijuana use and decrease marijuana use among girls who had initiated tobacco or marijuana use (Longshore et al, 2007). Researchers have suggested that prevention programs that target a decrease in ecstasy use should focus on the more common acute and sub-acute side-effects of ecstasy use in order to decrease approval of ecstasy use (Baggott, 2002;Carlson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention programs may need to consider different strategies in changing attitudes towards drug use once marijuana use has begun. For example, one school drug-prevention program based on three theoretical models (health belief model- Rosenstock et al, 1988, social learning model-Bandura, 1985, and the self-efficacy theory-Bandura, 1977) was able to decrease positive attitudes towards marijuana use and decrease marijuana use among girls who had initiated tobacco or marijuana use (Longshore et al, 2007). Researchers have suggested that prevention programs that target a decrease in ecstasy use should focus on the more common acute and sub-acute side-effects of ecstasy use in order to decrease approval of ecstasy use (Baggott, 2002;Carlson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Successful school prevention programs that focus on changing attitudes towards drug use such as the AlertPlus program (Longshore et al, 2007) should consider incorporating ecstasy-related material into their curriculum. Parents should also be better informed about the harms associated with ecstasy use and prevention efforts could emphasize better parental communication skills, which would, consequently, decrease parental permissiveness towards the use of ecstasy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ALERT Plus program did not have a signifi cant effect on drug use among at-risk boys. The authors hypothesized that this difference was due in part to the curriculum's focus on social learning and peer infl uences, which may impact adolescent girls more [44]. In addition, they suggested that girls may be more sensitive to the negative consequences of drinking.…”
Section: Treatment Responsementioning
confidence: 96%
“…A recent study assessed its effectiveness [44]. Girls reported signifi cantly lower rates of weekly alcohol, marijuana, and high-risk alcohol use compared with the control group.…”
Section: Treatment Responsementioning
confidence: 97%
“…Ello no quiere decir que todas las creencias erróneas estén desterradas, ni que existan grupos de población minoritarios que aún las mantienen. En la identificación de esos grupos deben centrarse los esfuerzos que se realicen en formación inicial para desterrar de manera definitiva estas creencias y lograr mayor eficacia en los programas preventivos (Longshore, Ellickson, McCaffrey y St Clair, 2007).…”
Section: Opiniones Y Creencias Sobre Las Drogasunclassified